System ról w rodzinach wiejskich w Polsce lat osiemdziesiątych - Nowak, Waldemar (Wydawnictwo Naukowe UAM, 2001)
The author has presented role syndrome in the following types of country families: farmers’ and farmer-workers’ families, families o f workers o f country socialized institutions, and non-agricultural families. In most o f the country families there exists traditional and conservative role division. It results from the division of country duties and work and also from rural mentality and culture. That explains bipolar divisions o f roles within country families into male and female roles closely related to productive functions. As far as the internal life o f a country family is concerned - considering especially interhuman relations, bringing up children and life-style - we should notice gradual and evolutional repelling of authority, formal and conservative roles leading to their democratization.
Role syndrome in country families in Poland of the 80s from historical point of view